Serum soluble T cell immunoglobulin mucin domain-3 as an early predictive marker for severity of acute pancreatitis; a retrospective analysis - Fushuang Wang; Minghui Zhu; Yao Meng; Min Lin (BMC Gastroenterology, 2022)
Abstract Background Early prediction of severe acute pancreatitis (SAP) plays an important role in timely treatment decisions. Soluble T cell immunoglobulin and mucin domain-3 (sTIM-3) has been applied as a potential biomarker for the prediction of many diseases, while its predictive ability for AP severity remains largely unexplored. In this study, we aimed to identify whether serum sTIM-3 could be used as an indicator of AP severity in the early stage of the disease. Methods A retrospective study was conducted. The enrolled AP patients should meet the 2012 Atlanta guideline and have an onset to admission ≤ 48 h. Results A total of 94 AP patients were enrolled in the current analysis, including 42 (45%), 35 (37%), and 17 (18%) patients were diagnosed as mild AP (MAP), moderately SAP (MSAP), and SAP, respectively. SAP patients had significantly higher the white blood cells (WBCs) count, red blood cells (RBCs) count, C-reactive protein (CRP) level, direct bilirubin level, creatinine and procalcitonin levels compared with MAP and MSAP patients. Among SAP and MSAP patients, significantly higher APACHE II, BISAP, and MCTSI scores were observed compared with MAP patients, and there was significant difference in APACHE II and BISAP scores between SAP and MSAP patients. Stepwise multivariate linear regression analysis showed that the concentrations of serum sTIM-3, as well as the BISAP and MCTSI scores, were significantly associated with the severity of AP. The areas under the ROC curve were 0.914 (95% CI, 0.865-0.963), 0.855 (95%CI, 0.742-0.968) 0.853 (95%CI, 0.768-0.938), and 0.746 (95%CI, 0.633-0.860) for BISAP score, APACHE II score, sTIM-3 level, and MCTSI score, respectively. Conclusions Serum sTIM-3 might be ultimately incorporated into a predictive system for assessing the severity of AP.